“Columns of the House” and Proud Workers: Greek Immigrant Women in Vancouver, 1954-1975 - Kalogeropoulou, Maria (Simon Fraser University, 2015)
In this thesis, I study the experiences of eight first-generation Greek immigrant women who moved to Vancouver between 1954 and 1975 by listening to and contextualizing their oral life histories. Looking at their lives before they immigrated, I explore how these women’s gender experiences were very much shaped by religion, class, and rural vis-à=vis urban locations in Greece. I also demonstrate that many exercised agency in this patriarchal culture, and that they were part of the decision-making process that led to immigration in search of a better life. After they immigrated to Vancouver, these women played an active part in supporting their families’ wellbeing, and some also contributed outside the household, offering their assistance to Greek communal organizations. Differences in class and working careers resulted in different narratives about immigration experiences, although the ideal of the kali noikokyra (good housewife) was consistent in their perceptions of proper Greek womanhood. Middle-class and working-class women also had different attitudes towards charitable work, religion, and the Greek community organizations. Both, however, actively contributed to the survival and settlement of Greek immigrant families in Canada. Overall, this thesis examines how gender, class, ethnicity, and religion affected Greek women’s identities before and after they immigrated in postwar period, and how their experiences of immigration altered their perspectives on the place of women in Greek families.